2009
DOI: 10.1016/j.ijid.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus and hepatitis C virus seroprevalence in rural areas of the southwestern region of Turkey

Abstract: Studies on seropositivity that depend on field analyses reflect the true population more accurately. We conclude that such field studies and public education activities for hepatitis B and C are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 7 publications
1
37
0
2
Order By: Relevance
“…Based on the published literature, the seroprevalence of HCV infection in Iranian general population is lower compared to other countries in the Middle East region. The general population-based studies that have assessed the prevalence of HCV infection in the middleeast countries include two studies from Turkey with the reported seroprevalence of 1% and 2.1% (21,22), a study from the Gaza strip with the reported seroprevalence of 2.2% (23), and a systematic review study from Yemen with the reported seroprevalence of 1.7% (24). Based on expert consensus, the seroprevalence of HCV infection is estimated to be 1.5% among United Arab Emirates general population (3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the published literature, the seroprevalence of HCV infection in Iranian general population is lower compared to other countries in the Middle East region. The general population-based studies that have assessed the prevalence of HCV infection in the middleeast countries include two studies from Turkey with the reported seroprevalence of 1% and 2.1% (21,22), a study from the Gaza strip with the reported seroprevalence of 2.2% (23), and a systematic review study from Yemen with the reported seroprevalence of 1.7% (24). Based on expert consensus, the seroprevalence of HCV infection is estimated to be 1.5% among United Arab Emirates general population (3).…”
Section: Discussionmentioning
confidence: 99%
“…HIV, hepatitis B, hepatitis C as well as Treponema palladium (syphilis) is the fourth infection that recommended by WHO to do screening as an attempt to get a blood transfusion is safe to the fourth infection due to this pathogen can cause chronic and infectious disease transmission risk being from donors to recipients of transfusions [1]. The results of this study are expected to provide benefit to reveal the problem infection in charities that seem healthy, provides information to formulate management strategies increase the safe blood supply, and provide an overview of the magnitude of the Infection prevalence of infectious disease through blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these data were based on retrospective analysis of cohorts comprising blood donors or risk groups. The data on prevalence of hepatitis C in Turkey is very limited, comprising a few studies from the southeastern and southwestern regions (9,10). A study by Tozun et al (11) was the largest populationbased study in Turkey, including 5460 participants from the rural and urban areas of 23 cities.…”
mentioning
confidence: 99%